2020
DOI: 10.1002/pbc.28730
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound has limited diagnostic utility in children with acute lymphoblastic leukemia developing pancreatitis

Abstract: Purpose: Acute pancreatitis (AP) due to chemotherapy-induced pancreatic injury is a common side effect of treatment for acute lymphoblastic leukemia (ALL), the most common childhood malignancy. The American College of Radiology recommends ultrasound (US) for initial imaging of AP in all populations to assess for ductal obstruction. However, US may be insensitive to diagnose and assess chemotherapy-associated AP. Methods and Materials: The institutional review board approved this retrospective study. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…This consensus reflects ultrasound's high sensitivity for gallstones and biliary obstruction, the modality's availability, and likely overemphasis on lack of ionizing radiation exposure. This consensus belies the moderate sensitivity and specificity of ultrasound for AP, with recent studies suggesting 47-52% sensitivity [8,9].…”
Section: Modalities For Imaging Pediatric Pancreatitis Ultrasoundsupporting
confidence: 59%
“…This consensus reflects ultrasound's high sensitivity for gallstones and biliary obstruction, the modality's availability, and likely overemphasis on lack of ionizing radiation exposure. This consensus belies the moderate sensitivity and specificity of ultrasound for AP, with recent studies suggesting 47-52% sensitivity [8,9].…”
Section: Modalities For Imaging Pediatric Pancreatitis Ultrasoundsupporting
confidence: 59%
“…Richardson study of clinically equivocal cases showed that a contrast-enhanced computed tomography or magnetic resonance imaging of the abdomen should be performed. [25] The accurate mechanism of AAP is unknown. The genetic risk factors associated with asparaginase-associated pancreatitis in pediatrics that have been found are PRSS1, Unc-51 like autophagy activating kinase 2, regulator of g protein signaling 6, Carboxypeptidase A2, 4-hydroxy-2-oxoglutarate aldolase 1, metallopeptidase with thrombospondin type 1 motif 17, Myb-binding protein 1A, sperm antigen with calponin homology and coiled-coil domains 1, asparagine synthetase (glutamine-hydrolyzing) and cystic fibrosis transmembrane conductance regulator.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS may help establish the diagnosis of early chronic pancreatitis, as areas of parenchymal fibrosis show decreased enhancement compared to the superior mesenteric artery [75]. However, a limitation of ultrasound in general for the assessment of pancreatitis is the frequent presence of overlying bowel gas that can obscure areas of necrosis and surrounding inflammatory changes [76]. Further study remains needed in children…”
Section: Pancreasmentioning
confidence: 99%